Praktik Wacana Iman di Era Digital: Khotbah Virtual GMIM Analisis Wacana Kritis Model Norman Fairclough - Juan Rasulivan Hendrik Lasut; Mariam Lidia Mytty Pandean; Djeinnie Imbang (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2026)
This study analyzes the transformation of faith discourse practices in the virtual sermons of the Christian Evangelical Church in Minahasa (GMIM) amidst the mediatization of religion. Employing a qualitative method with Norman Fairclough’s Critical Discourse Analysis approach, this research examines text, discursive practice, and socio-cultural dimensions to reveal power relations in the digital space. The findings indicate that the linguistic structure of sermons has significantly shifted to become more persuasive and egalitarian, utilizing synthetic personalization strategies to establish pseudo-intimacy with the congregation. Sermons are repackaged as concise, visual, and therapeutic content, adapting to the logic of social media algorithms and aesthetics. It is concluded that GMIM’s virtual sermons are not merely dogma transmission but an adaptive strategy reconstructing ecclesiastical authority from hierarchical to more humanist and motivational to maintain institutional relevance within digital culture.AbstrakPenelitian ini menganalisis transformasi praktik wacana iman dalam khotbah virtual Gereja Masehi Injili di Minahasa (GMIM) di tengah arus mediatisasi agama. Menggunakan metode kualitatif dengan pendekatan Analisis Wacana Kritis model Norman Fairclough, studi ini menelaah dimensi teks, praktik diskursif, dan sosiokultural untuk mengungkap relasi kuasa di ruang digital. Hasil penelitian menunjukkan bahwa struktur bahasa khotbah mengalami pergeseran signifikan menjadi lebih persuasif dan egaliter melalui strategi synthetic personalization guna membangun keintiman semu dengan jemaat. Khotbah dikemas ulang sebagai konten terapeutik yang ringkas dan visual, menyesuaikan diri dengan logika algoritma serta estetika media sosial. Disimpulkan bahwa khotbah virtual GMIM bukan sekadar transmisi dogma, melainkan strategi adaptif yang merekonstruksi otoritas gerejawi dari hierarkis menjadi lebih humanis dan motivasional demi menjaga relevansi institusi dalam budaya digital.